Telaah Buku Teks Mata Pelajaran Bahasa Jawa SMA Wiyata Basa Jawa ‘WIBAWA’ Berdasarkan Diagram FRY - Wulan, Sri Hertanti; Suwarna, Suwarna; Nurhidayati, Nurhidayati; Rubiyanto, Yayan (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
This study will reveal the quality of the textbooks used in DIY for high school students. From this research, the textbook standard will become a reference so that it can be used to achieve the goals of regional language education that have been mandated in the curriculum. This is a descriptive study. The data were collected from the WIBAWA book